44 Signal-to-Noise Ratio During Haemodynamic Optimisation of AV Delay is Improved more by Atrial Pacing than by Increasing Heart Rate. (6th June 2015) - Sharp, Alexander; Sohaib, Afzal; Willson, Keith; Mayet, Jamil; Hughes, Alun; Kanagaratnam, Prapa; Whinnett, Zachary; Kyriacou, Andreas; Francis, Darrel
Abstract : Background: Haemodynamic optimisation of atrioventricular delay has higher information content under fast atrial pacing. This study tests whether it is the presence of atrial pacing or the elevation of heart rate that is important. Methods: 43 patients with CRT underwent haemodynamic optimisation of AV delay using non-invasive beat-to-beat systolic blood pressure in three states: rest (A-sensing, 66 ± 11 bpm), slow atrial pacing (73 ± 11 bpm), and fast atrial pacing (92 ± 11 bpm). A 20-patient subset underwent a fourth optimisation, during exercise (80 ± 11 bpm). Results: Intraclass correlation coefficient (ICC, quantifying information content) was 0.30 ± 0.07 for resting sensed optimisation, 0.73 ± 0.04 for slow atrial pacing (p < 0.0001 versus rest-sensed), and 0.82 ± 0.02 for fast atrial pacing (p = 0.03 versus slow-paced). 83% of the increase in ICC, from sinus rhythm to fast atrial pacing, is achieved by simply atrially pacing just above sinus rate. Atrial pacing increased signal (blood pressure difference between best and worst AV delay) from 6.5 ± 0.6 mmHg at rest to 13.3 ± 1.1 mmHg during slow atrial pacing (p < 0.0001) and 17.2 ± 1.3 mmHg during fast atrial pacing (p < 0.001 versus slow atrial pacing) (Figure 1 ). Atrial pacing reduced noise (average SEM of systolic blood pressure measurements) from 1.6 ± 0.1 mmHg at rest to 1.4 ± 0.1 mmHg during slow atrial pacing (p = 0.02). At faster atrial pacing the noise was 1.5 ± 0.1 mmHg (p = 0.2 versus slow-paced, p = 0.3 versus resting sensed). In the exercise subgroup ICC was 0.23 ± 0.19 (p = 1 versus rest-sensed). Conclusions: Atrial pacing, rather than the increase in heart rate, contributes to ˜80% of the observed information content improvement from sinus rhythm to fast atrial pacing. This is predominantly through increase in measured signal.